Environmental engineering education for developing countries: framework for the future - Ujang, Zaini; Henze, M.; Curtis, Tom; Schertenleib, R.; Beal, L. L. (Elsevier Science B.V., Amsterdam, 2004)
This paper presents the existing philosophy, approach, criteria and delivery of environmental engineering education (E3) for developing countries. In general, environmental engineering is being taught in almost all major universities in developing countries, mostly under civil engineering degree programmes. There is an urgent need to address specific inputs that are particularly important for developing countries with respect to the reality of urbanisation and industrialisation. The main component of E3 in the near future will remain on basic sanitation in most developing countries, with special emphasis on the consumer-demand approach. In order to substantially overcome environmental problems in developing countries, E3 should include integrated urban water management, sustainable sanitation, appropriate technology, cleaner production, wastewater minimisation and financial framework